If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -1x = 5x + 4 Reorder the terms: 2 + -1x = 4 + 5x Solving 2 + -1x = 4 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 2 + -1x + -5x = 4 + 5x + -5x Combine like terms: -1x + -5x = -6x 2 + -6x = 4 + 5x + -5x Combine like terms: 5x + -5x = 0 2 + -6x = 4 + 0 2 + -6x = 4 Add '-2' to each side of the equation. 2 + -2 + -6x = 4 + -2 Combine like terms: 2 + -2 = 0 0 + -6x = 4 + -2 -6x = 4 + -2 Combine like terms: 4 + -2 = 2 -6x = 2 Divide each side by '-6'. x = -0.3333333333 Simplifying x = -0.3333333333
| 26-7/8x=2 | | -8x^2+46x+30=0 | | -5(w+7)(-w+2)=0 | | 4x+20=56 | | 48+20=56 | | 3(2x+1)=5x+3 | | (185-2x)+(x-20)=90 | | 4(5-3x)=44 | | 6(-10b+10)= | | X+3-2x=x-7 | | 2(x+3)-13=26+24-1 | | 0=-5/2x-2 | | 16x^2+40x+5=0 | | 16x-15=30x+11 | | 150/x=10 | | 2-2*2+2=0 | | 3squared+4=27 | | 3x+6y=350 | | -0.4w=-3 | | 6m+3=-15+2m | | 540/x=90 | | 16=JohnCENA | | -26=-7+9(b+8) | | -y^2+6y+x-9=0 | | 99=33x+9x+15 | | y-4=1/5(x-9) | | ln(x+3)=ln(6x-5) | | 35(6x-6)=1890 | | 4.9t^2-2t-50=0 | | 7×13/14--7 | | -4.9t^2+2t-50=0 | | -4z+9z=22 |